Exploring the Impact of Collaborative Reading Strategies in Improving Academic Reading Comprehension in Learners of English as a Foreign Language - Aminuddin, Rosidah Putri; Ferdiyanto, Feri; Zainuddin, Zainuddin (Journal of English Language and Education, 2026)
Academic reading comprehension is a crucial skill for EFL learners, as it enables them to understand complex texts and succeed in academic settings. Various studies have explored the use of collaborative reading strategies to improve students’ reading skills. However, most previous research has primarily focused on general reading comprehension, with limited attention given to academic reading in authentic EFL classroom contexts. This indicates a gap in understanding how collaborative reading strategies specifically support academic reading comprehension among EFL learners. Therefore, this study seeks to inestigate the impact of collaborative reading strategies in improving academic reading comprehension through a qualitative case study. The result of this are anticipated to contributed to provide practical findings for teachers in implementing collaborative learning approaches and contribute to the development of more effective academic reading instruction in EFL classrooms.